Assessing country compliance with circulating vaccine-derived poliovirus type 2 outbreak response standard operating procedures: April 2016 to December 2020. (6th April 2023) - Darwar, Roopa; Biya, Oladayo; Greene, Sharon A.; Jorba, Jaume; Al Safadi, Mohammad; Franka, Richard; Wiesen, Eric; Durry, Elias; Pallansch, Mark A.
Highlights: Successful outbreak response requires timely supplemental immunization activities. There are numerous sources of delayed response beyond the vaccine approval process. Several countries met multiple target indicators for successful outbreak response. Abstract: Background: Trivalent oral poliovirus vaccine (tOPV) was globally replaced with bivalent oral poliovirus vaccine (bOPV) in April 2016 ("the switch"). Many outbreaks of paralytic poliomyelitis associated with type 2 circulating vaccine-derived poliovirus (cVDPV2) have been reported since this time. The Global Polio Eradication Initiative (GPEI) developed standard operating procedures (SOPs) to guide countries experiencing cVDPV2 outbreaks to implement timely and effective outbreak response (OBR). To assess the possible role of compliance with SOPs in successfully stopping cVDPV2 outbreaks, we analyzed data on critical timelines in the OBR process. Methods: Data were collected on all cVDPV2 outbreaks detected for the period April 1, 2016 and December 31, 2020 and all outbreak responses to those outbreaks between April 1, 2016 and December 31, 2021. We conducted secondary data analysis using the GPEI Polio Information System database, records from the U.S. Centers for Disease Control and Prevention Polio Laboratory, and meeting minutes of the monovalent OPV2 (mOPV2) Advisory Group. Date of notification of circulating virus was defined as Day 0 for this analysis. Extracted process variables were compared with indicators in the GPEI SOP version 3.1. Results: One hundred and eleven cVDPV2 outbreaks resulting from 67 distinct cVDPV2 emergences were reported during April 1, 2016-December 31, 2020, affecting 34 countries across four World Health Organization Regions. Out of 65 OBRs with the first large-scale campaign (R1) conducted after Day 0, only 12 (18.5%) R1s were conducted by the target of 28 days after Day 0. Of the 89 OBRs with the second large-scale campaign (R2) conducted after Day 0, 30 (33.7%) R2s were conducted by the target of 56 days after Day 0. Twenty-three (31.9%) of the 72 outbreaks with isolates dated after Day 0 were stopped within the 120-day target. Conclusion: Since "the switch", delays in OBR implementation were evident in many countries, which may be related to the persistence of cVDPV2 outbreaks >120 days. To achieve timely and effective response, countries should follow GPEI OBR guidelines.